If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 14 + -1(x + 1) = 0 Reorder the terms: 2x + 14 + -1(1 + x) = 0 2x + 14 + (1 * -1 + x * -1) = 0 2x + 14 + (-1 + -1x) = 0 Reorder the terms: 14 + -1 + 2x + -1x = 0 Combine like terms: 14 + -1 = 13 13 + 2x + -1x = 0 Combine like terms: 2x + -1x = 1x 13 + 1x = 0 Solving 13 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 1x = 0 + -13 Combine like terms: 13 + -13 = 0 0 + 1x = 0 + -13 1x = 0 + -13 Combine like terms: 0 + -13 = -13 1x = -13 Divide each side by '1'. x = -13 Simplifying x = -13
| (6)n*n+7n=20 | | (6)n*n+7n=0 | | 1x+10+8=4 | | 15-g=23-29 | | (6)n*n+7n-20=0 | | (6)n*n+7-20=0 | | 2x+4(x-6)=-11-5(x-4) | | 3x^4=1536x | | 5x+7=-7+2x+20 | | 3+7(x-9)=3x-4 | | 6+2x-(x-3)=4(x-1)+22 | | 2-5(x+1)=9+x | | 1x+4-3=18 | | (10)p*p-19p+7=0 | | 12x-30=-27 | | 29=2.75+1.75(x) | | (x-6)(x-6)=(x+6)(x-12) | | (x-1)(x+1)=(x-5)(x+9) | | 5w+9=9w+33 | | -35=-11-3(y-1) | | x+3/(-6)=3 | | 216=2(2x)+2(x) | | 0.4t^4+7.72t^3-44.02t^2+476.9t= | | (x+11)(x-3)=(x+7)(x+9) | | 2(3x-1)=18 | | (x+2)*(x-7)=0 | | 3*-4-7=-5*-4-39 | | 22+2x=6x+62 | | -80=8(3x-1) | | -2(x+12)=18 | | 3x+2=130-x | | -7(x-9)=-14 |